2014
DOI: 10.3998/mij.15031809.0001.106
|View full text |Cite
|
Sign up to set email alerts
|

Placing International Media Production

Abstract: Abstract:Studies of contemporary media production have to grapple with the empirical, methodological, and theoretical challenges of internationalization. While cultural imperialism and the new international division of cultural labor theories have highlighted important power differentials internationally, they often lack empirical depth and focus on large traditional media companies and national, particularly Western, countries. In this short essay I consider how "spatialization" and the social production of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Similarly, co-working space director Lee and festival organizer Viktor maintain active relationships with government and arts agencies as a means of mediating between developers and potential sources of funding beyond investors, loans, and other market-oriented models emphasized in the game industry, in doing so influencing how governments "define and place" games as a medium and a business. 28 Mobilizing their expertise, social connections, and cultural capital as a "third who translates," each of these intermediaries uses their position to bridge across seemingly disparate cultural worlds. 29 Qualifying and adding value to cultural objects is a well-established function for cultural intermediaries, and several strategies for tastemaking and highlighting certain games among the chaff of a crowded indie market were discussed by participants involved in festival curation and event organizing.…”
Section: Brokering Translation and Ascribing Valuementioning
confidence: 99%
“…Similarly, co-working space director Lee and festival organizer Viktor maintain active relationships with government and arts agencies as a means of mediating between developers and potential sources of funding beyond investors, loans, and other market-oriented models emphasized in the game industry, in doing so influencing how governments "define and place" games as a medium and a business. 28 Mobilizing their expertise, social connections, and cultural capital as a "third who translates," each of these intermediaries uses their position to bridge across seemingly disparate cultural worlds. 29 Qualifying and adding value to cultural objects is a well-established function for cultural intermediaries, and several strategies for tastemaking and highlighting certain games among the chaff of a crowded indie market were discussed by participants involved in festival curation and event organizing.…”
Section: Brokering Translation and Ascribing Valuementioning
confidence: 99%
“…On the one hand, we want to understand the decision-making processes and the strategies developed by the content producers to insert their products into a global marketplace. On the other hand, we seek to advance research that follows Kerr’s (2014) call ‘to investigate how and in what ways industries, companies, workers, texts, and users get embedded in particular spaces while simultaneously being involved in global flows’ (p. 27).…”
Section: Introductionmentioning
confidence: 99%
“…Ramon Lobato recently observed that the incredibly large catalogues of Netflix offerings in "small" countries such as Guadeloupe and Martinique likely result from the fact that many Caribbean countries were lumped together with the USA when rights deals were negotiated(Lobato 2017: 246). Such tendencies are also present in other media sectors, such as those which lump together Europe, the Middle East and Africa for video game coding(Kerr 2014). 2 Small, Middle, Test: Rescaling Peripheral Media Markets…”
mentioning
confidence: 99%